Survey of Nebraska Farmers' Adoption of Dicamba-Resistant Soybean Technology and Dicamba Off-Target Movement. (9th November 2018) - Werle, Rodrigo; Oliveira, Maxwel C.; Jhala, Amit J.; Proctor, Christopher A.; Rees, Jennifer; Klein, Robert
Abstract: In 2017, dicamba-resistant (DR) soybean was commercially available to farmers in the United States. In August and September of 2017, a survey of 312 farmers from 60 Nebraska soybean-producing counties was conducted during extension field days or online. The objective of this survey was to understand farmers' adoption and perceptions regarding DR soybean technology in Nebraska. The survey contained 16 questions and was divided in three parts: (1) demographics, (2) dicamba application in DR soybean, and (3) dicamba off-target injury to sensitive soybean cultivars. According to the results, 20% of soybean hectares represented by the survey were planted to DR soybean in 2017, and this number would probably double in 2018. Sixty-five percent of survey respondents own a sprayer and apply their own herbicide programs. More than 90% of respondents who adopted DR soybean technology reported significant improvement in weed control. Nearly 60% of respondents used dicamba alone or glyphosate plus dicamba for POST weed control in DR soybean; the remaining 40% added an additional herbicide with an alternative site of action (SOA) to the POST application. All survey respondents used one of the approved dicamba formulations for application in DR soybean. Survey results indicated that late POST dicamba applications (after late June) were more likely to result in injury to non-DR soybean compared to early POST applications (e.g., May and early June) in 2017. According to respondents, off-target dicamba movement resulted both from applications in DR soybean and dicamba-based herbicides applied in corn. Although 51% of respondents noted dicamba injury on non-DR soybean, 7% of those who noted injury filed an official complaint with the Nebraska Department of Agriculture. Although DR soybean technology allowed farmers to achieve better weed control during 2017 than previous growing seasons, it is apparent that off-target movement and resistance management must be addressed to maintain the viability and effectiveness of the technology in the future.